2021
DOI: 10.1007/s10461-021-03307-8
|View full text |Cite
|
Sign up to set email alerts
|

Medical Mistrust and Stigma Associated with COVID-19 Among People Living with HIV in South Africa

Abstract: We evaluated COVID-19 stigma and medical mistrust among people living with HIV in South Africa. We conducted telephone interviews with participants in a prospective study of a decentralized antiretroviral therapy program. Scales assessing medical mistrust, conspiracy beliefs, anticipated and internalized stigma, and stereotypes specific to COVID-19 were adapted primarily from the HIV literature, with higher scores indicating more stigma or mistrust. Among 303 participants, the median stigma summary score was 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 56 publications
2
12
0
Order By: Relevance
“…Containment measures of COVID-19 taken in Ethiopia had a significant contribution to halting the spread of COVID-19 in Ethiopia; however, they had their own implications on HIV care and treatment services as the response from the patients with HIV as indicated. Transport disruption, partial lockdown that impaired mobility, and income reduction were significant factors in missing health care visits, which was in agreement with previous studies conducted in Ethiopia ( 13 , 42 ), and elsewhere in the world ( 43 50 ) that the COVID-19 containment measure had a significant impact on patients' access to healthcare facilities.…”
Section: Discussionsupporting
confidence: 91%
“…Containment measures of COVID-19 taken in Ethiopia had a significant contribution to halting the spread of COVID-19 in Ethiopia; however, they had their own implications on HIV care and treatment services as the response from the patients with HIV as indicated. Transport disruption, partial lockdown that impaired mobility, and income reduction were significant factors in missing health care visits, which was in agreement with previous studies conducted in Ethiopia ( 13 , 42 ), and elsewhere in the world ( 43 50 ) that the COVID-19 containment measure had a significant impact on patients' access to healthcare facilities.…”
Section: Discussionsupporting
confidence: 91%
“…The study’s findings showed that females were more likely to experience stigma than their male counterparts. This finding is consistent with previous studies carried out among patients with infectious diseases, including COVID-19, showing a higher prevalence of stigma among females than males ( Zandifar et al, 2020 ; James et al, 2019 ; Jarolimova et al, 2021 ). Several factors could be attributed to the higher prevalence of stigma in females.…”
Section: Discussionsupporting
confidence: 93%
“…Medical disinformation about COVID-19 may have ultimately exacerbated this pre-existing mistrust in healthcare. Understanding the high risk of being stigmatized with COVID-19 among those living with HIV is critical, as the repercussions on health outcomes can be severe [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…After the onset of the pandemic, the stigma of COVID-19 itself heightened other dubious conceptions about PLHIV. A prospective observational cohort study of PLHIV in South Africa reported over half of the participants either agreeing or strongly agreeing with survey questions assessing the stigma and stereotypes of COVID-19, as well as the lack of trust in healthcare providers [ 29 ]. It was determined that the association of stigma between HIV and COVID-19 did not occur during isolation.…”
Section: Discussionmentioning
confidence: 99%